Pengaruh Interaksi Penjualan dan Promosi Penjualan Terhadap Keputusan Pelanggan Pada Pelanggan Indihome di Wilayah Metro - Rahmat, Luthfi Izzudin; Septiana, Nani (Universitas Muhammadiyah Metro, 2021)
This study aims to determine whether a significant effect on the interaction of individual sales and sales promotion simultaneously has an influence on purchasing decisions of indihome customers in the metro area. to determine the most dominant variable on purchasing decisions and to analyze individual sales and sales promotions simultaneously have a positive effect on purchasing decisions. The research method used is quantitative research with associative methods. In this study, the analysis tool used is multiple correlation analysis to determine the dependent and independent variables with a computer program tool, namely SPSS 22 For Windows. The results of the research conducted by the researcher are 1) Individual Sales Variables have a positive effect on Purchasing Decisions, 2) Sales Promotion Variables cannot have a positive influence on Purchasing Decisions, 3) Simultaneously, Individual Sales and Sales Promotion variables have an effect on Purchasing Decisions at Indihome Customers in the Region. Metro.